Optimization of fermentation conditions for squalene production by heterotrophic marine microalgae Schizochytrium mangrovei PQ6 - Ha, Nguyen Cam; Minh Hien, Hoang Thi; Thom, Le Thi; Huong Quynh, Hoang Thi; Hong, Dang Diem (Academia Journal of Biology, 2017)
Squalene is currently known as chemopreventive agents in reducing the incident of coronary heart disease and cancer. It is also a strong antioxidant used extensively in the food and cosmetic industries. Microbial sources of squalene are being explored in recent years. The objective of this study was to investigate fermentation conditions of Schizochytrium mangrovei PQ6 for high squalene production in 30L bioreactor. Squalene production was influenced by various nutritional factors such as glucose, nitrogen, vitamins etc. and physical factors such as batch and fed-batch fermentation. Our study established that fed-batch fermentation with nitrogen source of 1.2% yeast extract and 6.4% monosodium glutamate and 0.4% mixture of vitamin B1, 6 and 12 as optimal culture condition for maximal production of squalene by S. mangrovei PQ6. In fed-batch culture, the glucose concentration feeding was added up to 22% into the culture at 36 h of fermentation. The maximum squalene production was achieved 6.9 ± 0.1 g/L at 48 h of fed-batch fermentation, respectively. The values were 2-3 times more than that in fed-batch cultivation without adding mixture of vitamins and 4-6 times more than that in batch cultivation. Our obtained results are a breakthrough for the development of alternative squalene source from heterotrophic marine microalgae of Schizochytrium mangrovei PQ6 species for health-promoting functional foods. Citation: Nguyen Cam Ha, Hoang Thi Minh Hien, Le Thi Thom, Hoang Thi Huong Quynh, Dang Diem Hong, 2017. Optimization of fermentation conditions for squalene production by heterotrophic marine microalgae Schizochytrium mangrovei PQ6. Tap chi Sinh hoc, 39(3): 349-358. DOI: 10.15625/0866-7160/v39n3.9130. *Corresponding author: hoangminhhien@yahoo.com; ddhong60vn@yahoo.com Received 6 January 2017, accepted 20 August 2017